Advances in display technology: augmented reality, virtual reality, quantum dot-based light-emitting diodes, and organic light-emitting diodes - Jihoon Kang; Geun Woo Baek; Jun Yeob Lee; Jeonghun Kwak; Jae-Hyeung Park (Journal of Information Display, 2024)
Virtual reality, augmented reality, quantum dot light-emitting diodes, and organic light-emitting diodes have progressed over the last two years. Key achievements in these displays are discussed in terms of device performance.